Linker DNA accessibility in chromatin fibers of different conformations: a reevaluation. - Zlatanova, J (1994)
New studies on chromatin fiber morphology, using the technique of scanning force microscopy (SFM), have caused us to reexamine recent analysis of nuclease digestion of chromatin. Chicken erythrocyte chromatin fibers, glutaraldehyde-fixed at 0, 10, and 80 mM NaCl, were imaged with the help of SFM. The chromatin fibers possessed a loose three-dimensional 30-nm structure even in the absence of added salt. This structure slightly condensed upon addition of 10 mM NaCl, and highly compacted, irregularly segmented fibers were observed at 80 mM NaCl. This sheds new light upon our previously reported analysis of the kinetics of digestion by soluble and membrane-immobilized micrococcal nuclease [Leuba, S. H., Zlatanova, J. & van Holde, K. (1994) J. Mol. Biol. 235, 871-880]. While the low-ionic-strength fibers were readily digested, the highly compacted structure formed at 80 mM NaCl was refractory to nuclease attack, implying that the linkers were fully accessible in the low-ionic-strength conformation but not in the condensed fibers. We now find that cleavage of the linker DNA by a small molecule, methidiumpropyl-EDTA-Fe(II), proceeds for all types of conformations at similar rates. Thus, steric hindrance is responsible for the lack of accessibility to micrococcal nuclease in the condensed fiber. Taken in total the data suggest that reexamination of existing models of chromatin conformation is warranted.